Readability Evaluation of Variable Handwritten Fonts on Different Screen Sizes Using Fuzzy Logic - Bratić, Diana; Stanić Loknar, Nikolina; Koren Ivančević, Tajana (International Journal of Interactive Mobile Technologies (iJIM), 2022)
According to the OpenType standard, variable font is a single font file which contains all style versions of one typeface family, as opposed to standard font families that use different files for each style version. Therefore, they are suitable for use on web because one file with all the necessary typeface styles is significantly smaller in size than classic families with multiple files. This shortens the font loading time, which enables wide range of typographical use on various devices. This paper investigates the readability of handwritten variable fonts in a responsible web environment on four screen sizes: extra small, small, medium, and large. Seven letter cuts were made from basic monoline handwritten font: thin, ultra-light, light, regular, semi-bold, bold, and ultra-bold. This paper presents model of readability evaluation using the fuzzy logic based postprocessing method for segmentation values related to evaluation criteria. Linguistic variable’s values are used to rate readability level against each of the criteria i.e., attributes. Prototype of a variable handwritten fonts are tested in responsive web environment, using CSS technology. The results show that readability evaluation has measurable output because the score combine various numeral factors affecting the readability of particular letter cut. Also, the results indicate that this type of font is not suitable for displays on extra small and medium screens such as mobile phones and tablets. That knowledge opens advanced possibilities to designers when designing for web because variable handwritten fonts are relatively simple, uniform and easily manageable. Using of proposed model in short time can show readability level of some font type on a new web.